Discourse on organisational memory in evidence-based management (Economic and Political Thought, 2020)
The article focuses on highlighting the approach of historical evidencebased management on the plane of organisational memory. The author treats the subject as a discursive interpretation. Based on the analysis of the literature on the subject, he presents an analogy between evidencebased management and management in the context of turning the past into the present. He describes his proposals as historical remembering, open to the reflections of practitioners and questions originating in medicine. The figure of the Hungarian doctor Ignaz Philipp Semmelweis, a forefather of evidence-based medicine, shows that ignoring scientific evidence in everyday practice can lead to a double loop of forgetting about values.
Keywords: evidence-based management, organisational memory, managerial competences